PERKEMBANGAN ONTOGENETIK DAUN TANAMAN KARET SEBAGAI PENANDA AWAL ADAPTASI TERHADAP CEKAMAN LINGKUNGAN DAN PATOGEN - Junaidi Junaidi; Atminingsih Atminingsih (Warta Perkaretan, 2017)
Clonal rubber leaves vary in shape, size, morphology and anatomy. Leaves development stages can be distinguished as A, B, C and D phase. In stage A, the leaflet hang vertically toward petioles. In stage B their color are light brown green with soft texture. In stage C, the leaflets are almost fully grown with firm laminae. In stage D, the leaflets have fully developed in nearly horizontal position. Physiologically, stage A and B are sink while stage C and D are source. The shorter transition from sink to source in new leaves is important response to environmental stress and pathogen. Therefore, leaves ontogenetical development can be used as early marker of plant adaptability to environment. Similar researches are necessary to be carried out using Indonesian specific clones and environment.